Facility-Level Factors Influencing Retention of Patients in HIV Care in East Africa - Rachlis, Beth; Bakoyannis, Giorgos; Easterbrook, Philippa; Genberg, Becky; Braithwaite, Ronald Scott; Cohen, Craig R.; Bukusi, Elizabeth A.; Kambugu, Andrew; Braithwaite, Ronald Scott; Cohen, Craig R.; Somi, Geoffrey R.; Geng, Elvin H.; et al. (PLOS ONE, 2016)
Losses to follow-up (LTFU) remain an important programmatic challenge. While numerous patient-level factors have been associated with LTFU, less is known about facility-level factors. Data from the East African International epidemiologic Databases to Evaluate AIDS (EA-IeDEA) Consortium was used to identify facility-level factors associated with LTFU in Kenya, Tanzania and Uganda. Patients were defined as LTFU if they had no visit within 12 months of the study endpoint for pre-ART patients or 6 months for patients on ART. Adjusting for patient factors, shared frailty proportional hazard models were used to identify the facility-level factors associated with LTFU for the pre- and post-ART periods. Data from 77,362 patients and 29 facilities were analyzed. Median age at enrolment was 36.0 years (Interquartile Range: 30.1, 43.1), 63.9%were women and 58.3%initiated ART. Rates (95% Confidence Interval) of LTFU were 25.1 (24.7–25.6) and 16.7 (16.3–17.2) per 100 person years in the pre-ART and post-ART periods, respectively. Facility-level factors associated with increased LTFU included secondary-level care, HIV RNA PCR turnaround time >14 days, and no onsite availability of CD4 testing. Increased LTFU was also observed when no nutritional supplements were provided (pre-ART only), when TB patients were treated within the HIV program (pre-ART only), and when the facility was open _4 mornings per week
Keywords: Facility; Level Factors; Influencing Retention; Patients; HIV; Care; East Africa